Dynamics of visual reversals from ambiguous spinning biological-motion and rigid structure-from-motion - Leo Poom (i-Perception)
Three-dimensional rigid structure-from-motion (SFM) and structure from nonrigid biological point-light motion stimuli are perceptually ambiguous. This study investigated the dynamics of perceived reversals in two cases: a spinning point-light walker (PLW) and a spinning rigid human figure in a walking pose (SFM). It specifically focused on two key questions: Could the facing-the-viewer bias (FTV) account for the reversals for spinning PLW? To what extent do motion cues from limb motions or configural cues from the human shape contribute to the perceived reversals? In Experiment 1, participants reported reversals with more than twice the frequency while viewing the upright and inverted PLW than for the rigid structures, but an FTV bias was observed only for the upright walker. The perception of an ambulating living human shape of typically encountered walkers in an upright position thus plays a crucial role in obtaining an FTV bias for these spinning stimuli. In Experiment 2, the human figures walked or rigidly moved along a circular path while facing the motion direction, spinning at the same rate as in Experiment 1. A strong initial FTV bias was then observed, but the reversal rate was substantially reduced compared to reversals when spinning on the same spot. These findings highlight theoretically interesting distinct temporal dynamics of reversals and biases between biological motion and rigid SFM. It is argued that the differences in reversals between conditions have a common cause in the form of past experiences that differ between conditions.